Land Assurance Process Execution Property Rights Of Indigenous Which Still In The Application Process Rights Used As Credit Guarantee - Daniel Budi Hardwianto; Akhmad Khisni (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2018)
This study examines the weaknesses in the execution process guarantee of property rights of indigenous land is a wedge legal certainty between Debtor and Creditor. The study also describes some of the views that aims to provide a solution to a process execution guarantee of property rights of indigenous land is still in the process of increasing the rights as loan collateral. This study uses normative juridical research method, namely the use of library materials or secondary data as the basis for research related to the Security Law, Contract Law and Land Law, as well as interviews with several parties. This study is a study that aims to find the problems as a result of activities or programs that have been implemented or may be called as a research Prescriptive. Credit Guarantees of property rights in land there is very risky because there is no umbrella law on which the creditor to carry out the execution process if the Borrower defaults, so it is necessary rigor in the process of granting the Credit Guarantee. Indigenous land rights certainly has weaknesses in its status because it has not been registered at the land office. With the weakness and absence umbrella clear laws that, it needed the additional requirements of the creditors if it wants to receive Guarantee Credit in the form of land property rights of indigenous in order to guarantee legal certainty in the execution process guarantees, one of the solutions that can be taken is to increase the land status become ownership Right.Keywords: Excecution Land Security; Indigenous Property Rights; The Application Rights; Credit Guarantees.